The Influence of HDI on the Unemployment Level in DKI Jakarta - M.A.S Sridjoko Darodjatun; Zaenudin; Bono Prambudi (Kusuma Negara Business School, 2020)
This study analyzes the Effect of the Human Development Index on the Unemployment Rate in DKI Jakarta. The problems in this research are (i) How is the development of the unemployment rate in DKI Jakarta; (ii) How is the development of the Human Development Index (HDI) in DKI Jakarta; (iii) How does the Human Development Index (HDI) affect the unemployment rate in DKI Jakarta. This research was conducted in three stages. The first stage is the preparatory stage of the research, including identifying problems and inventory data. The second stage is the stage of how to analyze the data obtained, and the third stage is the stage of testing the hypothesis and drawing conclusions. From this research, it can be seen that the correlation between improving the quality of human resources and reducing the unemployment rate in Jakarta